Direct Regulation of Hyperpolarization-Activated Cyclic-Nucleotide Gated (HCN1) Channels by Cannabinoids - Mayar, Sultan; Memarpoor-Yazdi, Mina; Makky, Ahmad; Eslami Sarokhalil, Romina; D'Avanzo, Nazzareno (Frontiers in Molecular Neuroscience, 2022)
Cannabinoids are a broad class of molecules that act primarily on neurons, affecting pain sensation, appetite, mood, learning and memory. In addition to interacting with specific cannabinoid receptors (CBRs), cannabinoids can directly modulate the function of various ion channels. Here we examine whether cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC), the most prevalent phytocannabinoids in Cannabis sativa, can regulate the function of hyperpolarization-activated cyclic-nucleotide gated (HCN1) channels independently of CBRs. HCN1 channels were expressed in Xenopus oocytes since they do not express CBRs, and the effects of cannabinoid treatment on HCN1 currents were examined by two-electrode voltage clamp. We observe opposing effects of CBD and THC on HCN1 current, with CBD acting to stimulate HCN1 function, while THC inhibited current. These effects persist in HCN1 channels lacking the cyclic-nucleotide binding domain (HCN1ΔCNBD). Changes to membrane fluidity examined by treating cells with TX-100 inhibited HCN1 current, however, had more pronounced effects on the voltage-dependence and kinetics of activation than THC, suggesting this is not the primary mechanism of HCN1 regulation by cannabinoids. Our findings may contribute to the overall understanding of how cannabinoids may act as promising therapeutic molecules for the treatment of several neurological disorders in which HCN function is disturbed.